The Measurement of the Dermal Bioavailability of Potentially Harmful Organic Soil Contaminants - Lort, Jack A. L. (2022)
Currently only one value is used to predict the human health risk of the dermal absorption of polycyclic aromatic hydrocarbons (PAH) from soil for contaminated land risk assessments. Research has shown that soil PAH dermal bioavailability differs between soils, and additionally that differences in skin physiology results in variation in the quantity of PAH absorbed. The current PAH dermal bioavailability value used in risk assessments was generated using soil spiked with radiolabelled PAH in a solvent, overestimating PAH soil mobility and therefore creating uncertainty in the dermal bioavailability value. Consequently, this study aims to develop a lab-based method to quantify the in vitro dermal absorption of native PAH from ‘real-world’ soils to produce soil-specific PAH dermal bioavailability values. PAH dermal bioavailability is defined here as: “The fraction of the PAH concentration that is absorbed into and/or through the skin”.